ANALISIS MAQASHID SYARIAH PEMANFAATAN SMARTPHONE SEBAGAI MEDIA PEMASARAN ONLINE PADA PELAKU WIRAUSAHA - Azizah Mursyidah; Siti Maspupah (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2023)
This study aims to determine the analysis of maqashid sharia on the use of smartphones as an online marketing medium for entrepreneurs during the Covid-19 period. As for the maqashid sharia, according to Imam Al-Ghazali, it is reflected in five main things, namely hifdz ad-Din (safeguarding religion), hifdz an-Nafs (safeguarding the soul), hifdz al-aql (safeguarding the mind), hifdz al-Mal (safeguarding property) , and hifdz an-Nasl (guarding offspring). The research method used is descriptive qualitative, data collection was carried out using interviews and questionnaires. The sample of this study was 30 participants, with the sampling technique in this study used on the basis of non-probability sampling with purposive sampling technique, namely samples taken with certain considerations/criteria, and snowball sampling, namely the addition of the sample was stopped when the data was saturated. or from various informants, both old and new, not providing any new data. The results of this research are the analysis of Maqashid Syariah on the use of smartphones as an online marketing medium for entrepreneurs in 3 villages which fall into the very appropriate category with an average percentage of 92%. There were obstacles faced by entrepreneurs in the 3 covid-19 villages causing a decline in the community's economy which resulted in reduced consumer buying interest, because the community prioritized or prioritized buying basic daily needs; the number of new competitors, the high cost of operations and raw materials, the presence of covid-19 financial reports or entrepreneurial income is decreasing, this is a threat to entrepreneurs